New Ways to Deal with Omni-Channel Services: Opening the Door to Synergies, or Problems in the Horizon? - Reis, João Carlos Gonçalves dos (2017)
This article aims to investigate organizational synergies in the omnichannel service context. In doing so, it discloses new omni-channel trends and discusses its implications for managers and academics. It uses a qualitative multimethod approach, which includes more than one method of collecting data to generate comprehensiveness and rich knowledge, namely: a systematic literature review and a case study. The transition to an omni-channel service requires companies to overcome many organizational challenges and is compelling academics and practitioners to focus on its operations management. The results indicate that organizational synergies are changing the omni-channel landscape and may provide several opportunities for gaining competitive advantages by implementing new technologies (e.g. m-payments), and anticipating customer needs (e.g. multi-brand experience). It is possible that these organizational synergies are transcending the omni-channel concept, creating new trends, but to confirm this hypothesis further investigation is needed.